Review of research on evaluating the ecological security of cultivated land - He, Yinjie; Wu, Dafang; Liu, Yanyan; Zhu, Hong (Frontiers in Environmental Science, 2023)
Cultivated land provides fundamental land-related resources, and its ecological security is thus an important means of protecting it. The ecological security of cultivated land has emerged as an important and challenging area of research in recent years. In this study, the authors summarize the progress in research on the evaluation of the ecological security of cultivated land through visual analysis. We review the concepts, characteristics, driving factors, scales and methods of evaluation, technologies, and simulations used in the relevant literature. The results show that: while the relevant concept has been preliminarily established, research on the ecological security of cultivated land remains in its infancy and comprehensive work on the subject is lacking. Prevalent research has mainly focused on analyzing the current situation, but lacks a dynamic analysis of the driving mechanism of the ecological security of cultivated land based on simulations. This has made it difficult to understand the spatiotemporal mechanism of the ecological security of cultivated land. Future research in the area should discuss the complex driving mechanism of interactions between the social economy system and the ecological system and focus on an integrated model to assess its dynamic spatial and multi-scale characteristics of ecological security of cultivated land because this can inform the theory of protecting cultivated land and the design of plans for land use to mitigate global climate change.